Equilibrium bitcoin pricing - Bruno Biais; Christophe Bisière; Matthieu Bouvard; Catherine Casamatta; Albert J. Menkveld (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
We offer an equilibrium model of cryptocurrency pricing and confront it to new data on bitcoin transactional benefits and costs. The model emphasises that the fundamental value of the cryptocurrency is the stream of net transactional benefits it will provide, which depend on its future prices. The link between future and present prices implies that returns can exhibit large volatility, unrelated to fundamentals. We construct an index measuring the ease with which bitcoins can be used to purchase goods and services, and we also measure costs incurred by bitcoin owners. Consistent with the model, estimated transactional net benefits explain a statistically signicant fraction of bitcoin returns.
Keywords: 330; Virtuelle Währung; Kosten-Nutzen-Analyse; Gleichgewichtsmodell